The Characteristics of Flour from Mango Seeds - Anggraini, Anggraini; Aprillia, Selfi; Aktawan, Agus (Journal of Agri-Food Science and Technology, 2023)
Indonesia produces 3,308,895 tons of mangoes in 2022. One type of mango in Indonesia is mango golek. Golek mango seeds can be processed into flour as a source of carbohydrates. The research contribution is the feasibility of golek mango seed flour based on SNI 3751:2009. Proximate analysis was used to determine the nutritional content of the golek mango seed flour. Flour is produced within 2 hours 30 minutes where the temperature variations are 80, 85, 90, 95, and 100 ℃. The proximate analysis consisted of the analysis of carbohydrate content, protein content, fat content, moisture content, ash content, and organoleptic tests. This study obtained an average carbohydrate content of 13.39%, an average protein content of 5.32%, an average water content of 0.80%, an average fat content of 0.33%, and a moderate ash content. 0.97%. The lower the yield of protein, water, fat, and ash, the lower the carbohydrate content, and vice versa. The results of the organoleptic test showed that the higher the temperature used during the oven, the darker the colour, the sharper the aroma, and the smoother the texture of the golek mango seed flour.